Housing Reform and Lawmaking in Ukraine: Between European Standards and Domestic Challenges - Hudima, Tetiana; Ustymenko, Volodymyr; Soshnykov, Anton; Oliukha, Vitalii (European Journal of Sustainable Development, 2025)
This article examines the implications of draft law ? 12377 “On the Fundamental Principles of Housing Policy” currently under consideration in Ukraine, with a particular focus on the regulation of service housing. The study argues that, in its current form, the draft poses significant legal and social risks, including potential violations of constitutional guarantees - such as the right to housing, the right to property, and the principle of legal certainty - as well as inconsistency with European human rights standards. The article evaluates the draft through the lens of the European Convention on Human Rights (Articles 1 of Protocol ? 1 and 8), the European Social Charter, and the European Pillar of Social Rights. Drawing on comparative legal analysis, the paper identifies critical gaps in the proposed regulation - particularly the absence of transitional provisions, the introduction of paid rental without safeguards, and the lack of mechanisms to address legitimate expectations of long-term residents. The article proposes legal amendments aimed at aligning the reform with the principles of proportionality, social justice, and good governance. Special attention is given to the principle of preventing unintended consequences, which the author recommends integrating as a foundational element of Ukraine’s lawmaking process to ensure that vulnerable groups are adequately protected during systemic legal transformations. By linking housing security to broader questions of social sustainability and institutional resilience, the article contributes to the scholarly debate on sustainable legal reform and inclusive urban development within the framework of the Sustainable Development Goals (SDG 11 and SDG 16). Keywords: service housing, housing policy reform, legal certainty, legitimate expectations, European Convention on Human Rights, social protection, unintended consequences, better regulation, transitional justice, Ukraine